Unraveling dynamic factors in Dialectic Behavioural Treatment for Adolescents (DBT-A): A study protocol - Anneke de Weerd; Anne A. Krabbendam; Agaath Koudstaal; Joep Sins; Jacquelijne Schraven; Robert R. J. M. Vermeiren; Jantine Roeleveld; Elisabeth Koopman-Verhoeff; Laura A. Nooteboom (PLoS ONE, 2026)
Dialectical Behavioural Therapy for Adolescents (DBT-A) is an effective treatment for adolescents exhibiting features of borderline personality disorder (BPD). However, some do not benefit, potentially leading to major negative outcomes later in life. Previous quantitative studies have highlighted the importance of dynamic (changeable) factors in determining treatment success, including the therapeutic alliance, emotional dynamics between therapist and adolescent, and the motivation of those involved. Nevertheless, the specific contribution of these factors to the therapeutic process and perceived treatment success remains unclear. This study protocol outlines a multicenter, qualitative longitudinal study designed to explore how dynamic factors in DBT-A are experienced by adolescents, parents, and therapists at various stages of therapy. The study will track treatment journeys (trajectories) of fifteen youth during DBT-A therapy across four child and adolescent psychiatry institutions in the Netherlands. The triad of adolescent, parent(s), and therapist will be interviewed separately at four time points during treatment: at the start and after three, six, and nine months (resulting in 180 interviews in total). The semi-structured interviews, based on a theoretical framework, will be analyzed using reflexive thematic analysis, employing a combination of deductive framework analysis and inductive open coding methods. By bringing together the triad of perspectives, and monitoring how these perspectives evolve over time, this study will yield valuable, practice-based insights into how dynamic factors unfold during DBT-A. Insights from this study will offer therapists specific, actionable guidance for modifying dynamic factors to better address the unique needs of adolescents with BPD features.